2021
DOI: 10.3390/microorganisms9061339
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of MicroRNA-126 Promotes Cell Growth in Marek’s Disease

Abstract: During latency, herpesvirus infection results in the establishment of a dormant state in which a restricted set of viral genes are expressed. Together with alterations of the viral genome, several host genes undergo epigenetic silencing during latency. These epigenetic dysregulations of cellular genes might be involved in the development of cancer. In this context, Gallid alphaherpesvirus 2 (GaHV-2), causing Marek’s disease (MD) in susceptible chicken, was shown to impair the expression of several cellular mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…They were grown at 41°C with 5% of CO 2 . Reactivation was induced by treatment of either 3 mM NaBu or 5 μM 5’azacytidine (Merck) and was verified by the expression of VP5 as previously described ( 51 , 80 , 81 ).…”
Section: Methodsmentioning
confidence: 99%
“…They were grown at 41°C with 5% of CO 2 . Reactivation was induced by treatment of either 3 mM NaBu or 5 μM 5’azacytidine (Merck) and was verified by the expression of VP5 as previously described ( 51 , 80 , 81 ).…”
Section: Methodsmentioning
confidence: 99%
“…Small RNA-seq analysis identified 54 novel miRNAs that were differentially expressed in MDV and control birds ( 64 ). The study demonstrated that miR-126 plays a role in suppressing tumors in Marek’s disease lymphoma ( 65 ). A potential regulatory network of miR-29b-3p and its target gene was identified, which regulates the characteristics of the MD lymphoma transformation ( 66 ).…”
Section: Mirnas Involved In Poultry Diseasesmentioning
confidence: 98%
“…Gennart and Petit et al investigated the role of a cellular micro RNA, miR-126, in MDV infection. Interestingly, miR-126 is known to play key roles in human cancers as well [ 13 ].…”
mentioning
confidence: 99%